AI cheerleaders: Public relations, neoliberalism and artificial intelligence. (May 2019) - Bourne, Clea
Public relations' (PR) professional habitus is defined by a relentless focus on optimism and futurity. This professional habitus renders PR indispensable to the corporate world after crisis, when new, potentially controversial, growth strategies must be sold-in to stakeholders. This article argues that PR's professional habitus is heavily influenced by neoliberalism, an ideology which 'confidently identifies itself with the future'. The discussion is timely, as 21st-century neoliberal capitalism becomes redefined by artificial intelligence (AI). The article combines PR theory, communications theory and political economy to consider the changing shape of neoliberal capitalism, as AI becomes naturalised as 'common sense' and a 'public good'. The article explores how PR supports AI discourses, including promoting AI in national competitiveness and promoting 'friendly' AI to consumers, while promoting Internet inequalities. The article concludes that the PR profession's myopia regarding the implications of promoting AI and neoliberalism is shaped by poor levels of diversity in the PR profession.